Three-fifths - Vercher, John (Agora Books an imprint of Polis Books, 2019)
"Pittsburgh, 1995. The son of a black father he's never known, and a white mother he sometimes wishes he didn't, twenty-two year-old Bobby Saraceno has passed for white his entire life. Raised by his bigoted maternal grandfather, Bobby has hidden the truth about his identity from everyone, even his best friend and fellow comic-book geek, Aaron, who has just returned home from prison a newly radicalized white supremacist. Bobby's disparate worlds crash when, during the night of their reunion, Bobby witnesses Aaron mercilessly assault a young black man with a brick. Fearing for his safety and his freedom, Bobby must keep the secret of his mixed race from Aaron and conceal his unwitting involvement in the crime from the police. But Bobby's delicate house of cards crumbles when his father enters his life after more than twenty years, forcing his past to collide with his present."--Amazon.